USO DE MEDICAMENTOS E FATORES ASSOCIADOS À UTILIZAÇÃO DE ANTIMICROBIANOS EM CRIANÇAS DE 13 A 35 MESES DA COORTE BRISA. - FURTADO, Danielle França (2017)
To analyze the medication use and associated factors to antimicrobials use in children aged 13 to 35 months in the city of São Luis – MA. A descriptive, analytical and cross-seccional study was conducted using BRISA Cohort sample data at two moments: Stage of the birth from January to December 2010 and in the stage of the first follow-up from April 2011 to January 2013. The sample of this study was 3308 children aged 13 to 35 months. Descriptive analysis of socioeconomic, demographic and health variables was carried out. The medication use in the 15 days prior to the interview was classified by means of the Anatomical Therapeutic Chemical (ATC) and to analyze the factors associated with the use of antimicrobials the Poisson regression model with robust variance was adjusted with inclusion of the independent variables using the hierarchical approach. Of the children followed up, the use of at least one medication was 90.9%; at least one antimicrobial, considering antibacterial, antifungal, antiviral and antiparasitic drugs, was 23.8%. The medicines classified by the most used anatomic groups were: respiratory activity in 83.5%, followed by those in the nervous system 28.4%, by medicines of the alimentary tract and metabolism 23.5%, and anti-infectives of systemic use 10.5%. The factors associated with the use of antimicrobials after adjusted analysis were: Maternal perception about the child's health (Regular / Bad: PR = 1.37, p <0.001), post - birth morbidity (PR = 1.50, p <0.001) and time of breastfeeding (Suck between 3 and 6 months: PR = 1.34 p = 0.013). The high consumption of drugs reinforces the need to promote rational use for this age group, since the information about the effects of pharmacotherapy in the infant organism is limited. Factors associated with the use of antimicrobials point to the importance of these drugs in the health-disease process, allowing managers to better understand this process and the consequent implementation of actions directed at the health care of the child, with increased access to these medicines. Safe and appropriate to the specificities of infantile pharmacotherapy.